Modeling species invasions using thermal and trophic niche dynamics under climate change - Libralato, Simone; Caccin, Alberto; Pranovi, Fabio (Frontiers in Marine Science, 2015)
Changing marine temperatures modify the distributional ranges of natural populations, but the success of invasion of new areas depends on local physical and ecological conditions. We explore the invasion by thermophilic species and their ecosystem effects by simulating a sea surface temperature increase using a trophodynamic model for the northern Adriatic Sea (NAS), in which thermal and trophic niches are explicitly represented for each thermophilic non-indigenous species and native species. The NAS acts as a cul-de-sac for local species, preventing a further poleward migration as a response to temperature rise. In this situation, model results showed that effects of warming and invasion produced complex, non-linear changes on biomasses but never resulted in a complete overturn of a group of native species and/or a bloom of invasive ones. Despite this, the diversity index stabilizes at increased values after simulating invasion, possibly indicating that in such enclosed systems the establishment of invasive species could represent enrichment in ecosystem structure. In addition, the absence of complete species substitution clearly showed the contribution of resident species towards increasing the resilience, i.e. the capability of the system to cope with invasion without changing substantially. Contrasting scenarios highlighted that changes in ecosystem primary production and species adaptation had secondary effects in ecosystem structure, while results for scenarios with different exploitation levels indicated that fishing can destabilize community structure in these change contexts, e.g. reducing community resilience. The results confirmed the importance of an ecological niche approach to analyze possible effects of invasion and highlighted the complexity of dynamics linked to temperature-driven species invasion’, in terms of both the predicted strength of impacts and the direction of biomass change.